The Neuroprotective Effect of Short Chain Fatty Acids Against Sepsis-Associated Encephalopathy in Mice - Liu, Jiaming; Jin, Yangjie; Ye, Yanglie; Tang, Yahui; Dai, Shanshan; Li, Mengfang; Zhao, Guangju; Hong, Guangliang; Lu, Zhong-Qiu (Frontiers in Immunology, 2021)
Short chain fatty acids (SCFAs) are known to be actively involved in multiply brain disorders, but their roles on sepsis-associated encephalopathy (SAE) remain unclear. Here, we investigated the neuroprotective effects of SCFAs on SAE in mice. Male C57BL/6 mice were intragastrically pretreated with SCFAs for 7 successive days, and then subjected to SAE induced by cecal ligation and puncture. The behavioral impairment, neuronal degeneration and levels of inflammatory cytokines were assessed. The expressions of tight junction (TJ) proteins including occludin and zoula occludens-1 (ZO-1), cyclooxygenase-2 (COX-2), cluster of differentiation 11b (CD11b), phosphorylation of JNK and NF-κB p65 in the brain were measured by western blot and Immunofluorescence analysis. Our results showed that SCFAs significantly attenuated behavioral impairment and neuronal degeneration, and decreased the levels of IL-1β and IL-6 in the brain of SAE mice. Additionally, SCFAs upregulated the expressions of occludin and ZO-1 and downregulated the expressions of COX-2, CD11b, and phosphorylation of JNK and NF-κB p65 in the brain of SAE mice. These findings suggested that SCFAs could exert neuroprotective effects against SAE in mice.